Influence of Inclusion of Banana Meal in the Diet on Growth Performance of Pigs - Moreira, E.; Loor, K.; Gavilanes, P.; Muñoz, J.; Rodriguez, A.; Moro, A. (Indian Journal of Animal Nutrition, 2017)
The main objective of this study was to assess the effect of diets supplemented with banana meal (BM); obtained from agricultural waste) on pig growth performance. Nutritive value of by-product was carried out (banana meal, BM) using 16 growing pigs (Landrace × Pietrain) in four groups fed four diets with different BM levels. Each diet included BM in different proportions: commercial diet A (0% BM), other commercial diet B (0% BM), D10 experimental diet (10% BM) and D50 experimental diet (50% BM). Diet D10 showed comparable values for weight gain (36.12 kg) with diet A and B (32.43 and 33.00 kg) however, these values were higher that those in D 50 diet. D10 experimental diet did not affect feed conversion rate (FCR) was comparable to commercial diets. FCR values increased when BM was included at 50% level in the diet.